A waterborne polyurethane‐based hybrid fluorescent silicon quantum dot. Issue 35 (21st July 2022) - Gong, Chengbing; Xiao, Bihua; Hu, Xianhai; Xian, Yuxi; Wang, Ping; Yang, Yuqing; Luo, Xiang; Li, Mingjun; Liu, Jin; Ding, Yunsheng; Xu, Pei; Liu, Chao
Abstract: An amino‐hydroxy‐functionalized strongly fluorescent hybrid silicon quantum dots (znoSiQDs) were prepared by a green and simple method. Waterborne polyurethane‐based hybrid fluorescent silicon Quantum dots (znoSiQDs‐WPU) was prepared by a modified acetone method using znoSiQDs as chain extender. The structure and properties were also investigated by Fourier transform infrared spectroscopy (FT‐IR), thermogravimetric analyzer (TGA), fluorescence spectroscopy (FL), and so on. ZnoSiQDs was successfully connected to the polyurethane backbone by covalent bonding. ZnoSiQDs‐WPU can effectively shield UV in the range of 300–400 nm. Compared with WPU, the UV shielding range of znoSiQDs‐WPU is significantly larger, attributed to the direct band gap transition Γ → Γ. The fluorescence intensity of znoSiQDs‐WPU was dramatically enhanced compared with that of znoSiQDs. Compared with znoSiQDs, the maximum emission peak of znoSiQDs‐WPU is blue shifted at about 18 nm, which was related to the increased polarity of the imidazole chromophore. The luminous life of znoSiQDs‐WPU is up to 6.58 ns. The thermal stability of znoSiQDs‐WPU is improved by bonding znoSiQDs to the main chains of WPU. Furthermore, it is water as a solvent, especially suitable for safety, green, environment amity of materials. Abstract :